Upgrading of the Protein Content of Banana and Orange Peels by using Aspergilus Niger, Trichoderma Reesei and Penicilium spp - Adhikari, Rajan prasad; Baral, Madhav Prasad (Tribhuvan University Journal, 2011)
Not available. Key words: Aspergilus Niger; Trichoderma Reesei; Penicilium SPP Tribhuvan University Journal Vol XXI, No. 2, 1998 Page: 103-107 Uploaded date: 29 April, 2011